2017
DOI: 10.1177/1071100717706154
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes After Percutaneous Reduction and Fixation of Low-Energy Lisfranc Injuries

Abstract: Level IV, retrospective case series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 25 publications
(34 reference statements)
1
13
0
Order By: Relevance
“…Although some investigators reported that the open anatomic reduction and bridge plate fixation is the best way to treat Lisfranc injuries, 16 all of the reported cases were high-energy injury related with more than one column involved. Vosbikian et al 17 . reported a series of low-energy Lisfranc injuries with Lisfranc ligament disruption confirmed by MRI in 38 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Although some investigators reported that the open anatomic reduction and bridge plate fixation is the best way to treat Lisfranc injuries, 16 all of the reported cases were high-energy injury related with more than one column involved. Vosbikian et al 17 . reported a series of low-energy Lisfranc injuries with Lisfranc ligament disruption confirmed by MRI in 38 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of Lisfranc injuries can range from observation and nonoperative management, closed reduction and percutaneous pinning, ORIF, and PA in select circumstances. 1,12,16,24 There have been many studies analyzing differences in outcomes pertaining to management of these injuries. It has been found that worse outcomes are associated with more severe injuries.…”
Section: Discussionmentioning
confidence: 99%
“…This score has been validated in numerous and varying patient cohorts. 4,10 Though the treatment of Lisfranc injuries is variable and includes but is not limited to closed reduction and percutaneous pinning, open reduction and internal fixation (ORIF), and primary arthrodesis (PA), 1,12,16,24 the purpose of this study was to present long-term PROMIS-PF and VAS-FA scores in patients with Lisfranc injuries after ORIF. We hypothesized that following surgically treated Lisfranc injury, long-term patient-reported outcomes will represent a significant decrease in physical function as well as increased pain.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the 4 studies which they were analysed, it is important to mention three more studies relevant to the subject of this review (Table 1), which they were not included to meta analysis for minor reasons, such as different outcome score, type of injury not clearly defined, or not applicable follow up time etc. Vosbikian et al 16 studied 31 patients who sustained a low energy lisfranc injury, treated with a closed reduction and percutaneous fixation using a 4,0 mm fully threaded solid or cannulated screw. Average follow up time was 66 months and the average foot and ankle ability measure (FAAM) for activities of daily living (ADL) and FAAM for sport's activities was 94,2 and 90,4 respectively.…”
Section: Resultsmentioning
confidence: 99%